Peran Mahasiswa Progam Internship UNNES dalam Pengenalan Tari pada Kedutaan Besar Republik Indonesia di Manila. - Pramesti, Febriola Lintang; Kusumastuti, Eny (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the introduction of dance art at the Embassy of the Republic of Indonesia in the Philippines through an Internship Program carried out by students from Semarang State University. This research uses a qualitative approach with a case study approach through participatory observation, interviews, and documentation during the Internship period from October to November 2024. The results of this study show that dance art has a strategic location in the media of introducing Indonesian culture in the Philippines, dance performances are not only ceremonial but also part of a planned cultural diplomacy strategy. The implementation of Internship activities provides practical experiences for students such as involvement in performing art performances in both formal and informal events, participating in international activities, cultural collaboration between two countries, and learning dance for the diaspora. Thus, dance has proven to be effective in bridging differences in backgrounds, cultures and languages. Thus, the internship program at the Indonesian Embassy in Manila is a strategic means in the implementation of cultural diplomacy as well as a vehicle for contextual learning for students.